Increasing Activities and Learning Outcomes PPKn Through Make A Match Model Assisted Video Power Point - Erna Dwiarianti (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The initial reflection of the teacher does not use the media, students do not pay attention to the teacher's explanation during learning. To solve this problem by applying the cooperative model type Make A Match assisted with Video Power Point. Make A Match or finding a partner is a cooperative learning technique that can develop student abilities and is able to create an active and fun learning atmosphere for students. The research objective was to increase the activities and learning outcomes of class III students in the PPKn lesson content. This research is a classroom action research consisting of three cycles with the stages of planning, implementing action, observing, and reflecting. The subjects of the research were third grade students of SDN Wates 5, Magelang City. Data collection techniques used tests and non-tests. Cycle I students who completed after evaluation 78%, cycle II 85%, and cycle III 93%.